(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Vaccinations are at the center of renewed attention due to the effects produced by social networks on democratic processes. The public debate, in particular on the issues around vaccinations, has been polluted by misinformation and conspiracy theories. The theme is therefore examined by focusing on the issue of scientific evidence and the role of both science and the law in regulating issues of public interest. The paper also deals with specific burning issues such as the rights and duties of medical and paramedical personnel and the balance between the right to health and the right to education of children. In conclusion, some possible solutions are offered.